Comparación de la efectividad de la clarificación de jugo de caña (Saccharum officinarum) con tres tipos de mucílagos naturales - Murillo Vallejo, Diana Gabriela (2023)
The clarification of sugar cane juices is one of the most critical unit operations in the process of making honey, panela or alfeñiques; the separation of the impurities is by agglutination formed by the combined action of temperature, time and vegetable mucilage. The purpose was to compare the efficacy of the clarification of cane juice (Saccharum officinarum) with three types of natural mucilage extracted from nopal (Opuntia ficus-indica), cocoa shell CCN-51 (Theobroma cacao L) and aloe vera (Aloe). The experimentation was carried out considering two factors (A*B), with three levels each and 3 repetitions, where factor A: natural flocculant and factor B: percentage of mucilage. Mucilaginous solutions of cocoa shell CCN-51 and nopal and aloe vera were obtained with water, but not in sugarcane juice, and had a constant viscosity of 12 cP. The dosing of the mucilage solutions was carried out around 55 ºC and the filter cake was reduced when the juices reached 75 ºC. The experimental responses of the chromatic properties were examined in the Infostat statistical software, with the Shapiro Wilks test, noting that the data are not normally distributed; therefore, non-parametric tests such as Friedman and Holm were applied. The best treatment was the combination a1b1 corresponding to clarified sugar cane juice with cocoa shell mucilage CCN-51 and a dose of 1.5%, of which 3.94% of filter cake was reduced at the end of the clarification process and, the colorimetry indicators were lightness (L*) 43,211, chroma (C*) 23,974 and hue (H*) 80,762. Keywords: clarification, mucilage, luminosity, chroma, cane.